2004
DOI: 10.1302/0301-620x.86b6.14589
|View full text |Cite
|
Sign up to set email alerts
|

Does the femur roll-back with flexion?

Abstract: MRI studies of the knee were performed at intervals between full extension and 120 degrees of flexion in six cadavers and also non-weight-bearing and weight-bearing in five volunteers. At each interval sagittal images were obtained through both compartments on which the position of the femoral condyle, identified by the centre of its posterior circular surface which is termed the flexion facet centre (FFC), and the point of closest approximation between the femoral and tibial subchondral plates, the contact po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
102
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(127 citation statements)
references
References 6 publications
17
102
0
4
Order By: Relevance
“…The slight decrease in the MA, using the TF contact method, in terminal extension agrees with the fact that the tibiofemoral contact point moves anteriorly during this part of extension (Buford, Jr. et al, 1997;Pinskerova et al, 2004). Since one of these studies (Kellis and Baltzopoulos, 1999) used a slow extension movement with a simulated maximal extensor load and the others were static without load, it would appear that overall muscle loading did not alter the MA, when calculated using the TF contact method.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The slight decrease in the MA, using the TF contact method, in terminal extension agrees with the fact that the tibiofemoral contact point moves anteriorly during this part of extension (Buford, Jr. et al, 1997;Pinskerova et al, 2004). Since one of these studies (Kellis and Baltzopoulos, 1999) used a slow extension movement with a simulated maximal extensor load and the others were static without load, it would appear that overall muscle loading did not alter the MA, when calculated using the TF contact method.…”
Section: Discussionsupporting
confidence: 61%
“…As open MRI technology improves, experiments looking at the full range of motion will become available. Yet, in the range excluded from this study, the FHA is primarily static (Woltring, 1994), being guided by the circular posterior femoral condyles (Pinskerova et al, 2004). Thus, at higher knee angles, the MA likely continues to decrease with increasing knee angle, due to a posterior displacement of the patellar tendon line of action.…”
Section: Discussionmentioning
confidence: 92%
“…Second, our radiographs in flexion were nonweightbearing. Most but not all [18] published kinematic results are weightbearing, making it difficult to compare our nonweightbearing findings to prior literature. Johal et al [10] observed tibiofemoral movement in 10 weightbearing and nonweightbearing Caucasian knees using MRI and found tibial internal rotation with flexion was present in both groups but was a magnitude of rotation greater and occurred earlier with weightbearing.…”
Section: Discussionmentioning
confidence: 84%
“…Healthy knee kinematics show a rollback movement of the femur during flexion, particularly of the lateral femoral condyle, concomitant with tibial internal rotation [15,18,28]. Most studies show that the medial femoral condyle hardly moves anteroposteriorly from full extension to 120°of flexion, whereas the lateral femoral condyle moves posteriorly to a variable extent.…”
Section: Discussionmentioning
confidence: 99%